Pemanfaatan Limbah Keramik Sebagai Bahan Alternatif Campuran Agregat Kasar Pada Beton - Arif, Arif Arizal Firmansyah; Putu , Ariawan; Darmayasa , I Gusti Ngurah Putu; Ariana, Komang Agus (Universitas Pendidikan Nasional, 2023)
In every construction and renovation project, there is often waste that is rarely reused. The utilization of ceramic waste as a coarse aggregate in concrete can be an interesting alternative because ceramic waste shares characteristics and properties similar to coarse aggregate materials, such as hardness, and has the potential to reduce negative environmental impacts and the depletion of raw materials. Therefore, this research adopts an experimental method at the laboratory of the National Education University in Denpasar by creating five different variations of cylindrical specimens, each with three samples. The ceramic waste variations used are 0%, 10%, 15%, 20%, and 40%. By using an FAS value of 0.6, the slump value was obtained, where the larger the ceramic waste mixture value, the smaller the slump value, as this occurs due to the water absorption value in the ceramic waste being 10.51%. However, despite this, the slump value still falls within the planned range of 5.0 cm to 12.0 cm, and for the planned compressive strength value, which is 175 kg/m2, the highest average concrete strength value is found in the 0% variation, which is 16.01 MPa or equivalent to 192.83 kg/cm2. The concrete with a 10% variation has a compressive strength of 15.21 MPa or 183.25 kg/cm2, the concrete with a 15% variation has a compressive strength of 15.01 MPa or 180.82 kg/cm2, the concrete with a 20% variation has a compressive strength of 13.64 MPa or 164.38 kg/cm2, and the concrete with a 40% variation has a compressive strength of 9.87 MPa or 118.96 kg/cm2. This research can be used as additional literature or as an evaluation material for further research.